2018
DOI: 10.1590/0100-6991e-20181779
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor follow-up after bariatric surgery

Abstract: there was a progressive loss of follow-up from the second postoperative year on. Among the factors analyzed, only the variable "excess weight" greater than 49.95kg in the preoperative period was associated with loss of medical-surgical follow-up. In the 48th month of the postoperative period, there was a higher prevalence of loss of medical-surgical follow-up for patients outside the perimeter of the city of Recife (51%, p=0.052).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
(42 reference statements)
0
6
1
Order By: Relevance
“…International surveys indicate progressively low rates of consultation attendance in the postoperative period: 50 % in the first year, 30 % in two years, and < 10 % in ten years [9]. In our study, the general consultation attendance was…”
Section: Discussioncontrasting
confidence: 48%
“…International surveys indicate progressively low rates of consultation attendance in the postoperative period: 50 % in the first year, 30 % in two years, and < 10 % in ten years [9]. In our study, the general consultation attendance was…”
Section: Discussioncontrasting
confidence: 48%
“…Self-reported depression was found mostly in female (p=0.041) and young patients (p=0.042) 6 , supporting the results of King (2019). Depression’s impact on surgical outcomes is not only limited to the statistical results but also it impairs cooperativeness 11 and impedes motivation, both of which interfere with overall adherence to protocols, diet 4 , physical activity 25 , behavioral change, and long-term follow-up adherence 8 . All of these are considered critical protectors for WR, long-term surgical success, and quality of life 9 , 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…WR was calculated using both the nadirs postsurgical weight considering a cutoff point of 15% and the percentage of maximum weight loss considering a cutoff point of 20% 4 , 5 .…”
Section: Methodsmentioning
confidence: 99%
“…6 One study found that there is a loss of progressive follow-up of patients in medicalsurgical consultations starting from the second postoperative year. 7 Sexuality in women is closely linked to subjective aspects related to psychological, cultural, and social conditions, in addition to body perception. 8 In addition to having negative repercussions for female sexuality, obesity also affects ovulation, which culminates in fertility impairments.…”
Section: Discussionmentioning
confidence: 99%